Defining digital literacy - What do young people need to know about digital media? - David Buckingham (Universitetsforlaget, 2015)
This article offers a rationale for the notion of «digital literacy» in education. Pointing to some of the limitations of previous proposals in this field, it outlines a framework based on four key concepts drawn from media education. It applies these concepts to the World Wide Web and to computer games, and discusses the role of digital media production by students in developing digital literacy. The article emphasises the importance of developing critical approaches to digital media as a necessary prerequisite for using them as resources for learning.